DISPARITY IN JUDICIAL DECISIONS ON ROBBERY RESULTING IN THE DEATH OF THE VICTIM - Indah Triskayanti (Lex LATA, 2026)
As a state governed by law, Indonesia should firmly uphold the principle of the rule of law in exercising its judicial power namely, a state that administers all aspects of its governance based on law. Judges are granted authority by legislation to receive, examine, and decide criminal cases based on the principles of independence, honesty, and impartiality in court proceedings. In practice, however, disparities frequently arise in judges' decisions when adjudicating and imposing sentences in criminal cases. A judge's considerations in imposing criminal sanctions consist of juridical considerations and non-juridical considerations. Theft is a crime committed against a person's property, and may even involve physical loss, when carried out with violence that can result in injury or even loss of life. Theft with violence is regulated under Article 365 of the Indonesian Criminal Code (KUHP). Pursuant to Article 1 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, the independence of a judge is fully guaranteed. The research problems addressed by the author are: how judges consider the imposition of criminal sanctions in cases of theft with violence resulting in the death of the victim, with reference to Decision Number 212/Pid.B/2021/PN.Gns and Decision Number 344/Pid.B/2021/PN.Lht; and what guidelines judges should follow in imposing sentences so as not to create disparities in sentencing. The research findings indicate that judges frequently create sentencing disparities when handing down criminal decisions. To prevent such disparities in the future, judges can apply the prevailing legal rules in force in Indonesia.